Magnetic attraction forces between permanent magnet group arrays in a mobile magnetic clamp for pocket machining. (November 2015) - Mahmud, A.; Mayer, J.R.R.; Baron, L.
Abstract: A mobile magnetic clamp was recently tested for pocket milling on a fuselage panel. The magnetic clamps need to provide sufficient support force against the milling thrust force and sufficient drag force to overcome the frictional force. Triangular arrays of cylindrical permanent magnets are used. Axial magnetic attraction forces between magnet groups are calculated based on recently published formula at various axial heights and lateral displacements. A model is here proposed to estimate lateral magnetic attraction forces as a function of lateral displacement between two cylindrical permanent magnets. Experiments conducted using a dynamometer table to validate the measured axial and lateral magnetic forces strongly support the analytically predicted magnetic forces.